Human erythrocytes: cytoskeleton and its origin - Nigra, Ayelén Denise (2020)
In the last few years, erythrocytes have emerged as the main determinant of blood rheology. In mammals, these cells are devoid of nuclei and are, therefore, unable to divide. Consequently, all circulating erythrocytes come from erythropoiesis, a process in the bone marrow in which several modifications are induced in the expression of membrane and cytoskeletal proteins, and different vertical and horizontal interactions are established between them. Cytoskeleton components play an important role in this process, which explains why they and the interaction between them have been the focus of much recent research. Moreover, in mature erythrocytes, the cytoskeleton integrity is also essential, because the cytoskeleton confers remarkable deformability and stability on the erythrocytes, thus enabling them to undergo deformation in microcirculation. Defects in the cytoskeleton produce changes in erythrocyte deformability and stability, affecting cell viability and rheological properties. Such abnormalities are seen in different pathologies of special interest, such as different types of anemia, hypertension, and diabetes, among others. This review highlights the main findings in mammalian erythrocytes and their progenitors regarding the presence, conformation and function of the three main components of the cytoskeleton: actin, intermediate filaments, and tubulin.